2018
DOI: 10.3892/etm.2018.7087
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑146b induces the PI3K/Akt/NF‑κB signaling pathway to reduce vascular�inflammation and apoptosis in myocardial infarction by targeting PTEN

Abstract: The aim of the present study was to investigate the function of microRNA-146b on myocardial infarction and the mechanism. An MTT assay, Annexin V/propidium iodide (PI) apoptosis assay, ELISA kits, western blot analysis and a caspase-3/8 activity assay were used to measure cell growth, vascular apoptosis inflammatory factors, and the B-cell lymphoma 2-associated X protein (Bax), phosphatase and tensin homolog (PTEN), phosphoinositide 3-kinase (PI3K)/Akt/nuclear factor (NF)-κB signaling pathway. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“… 2019 ; Zhao et al. 2019 ). Therefore, we speculated that QRHX may activate autophagy to exert myocardial protective function.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Zhao et al. 2019 ). Therefore, we speculated that QRHX may activate autophagy to exert myocardial protective function.…”
Section: Discussionmentioning
confidence: 99%
“…Sprouty homolog 1 is located on chromosome 4 of human beings and has been reported to participate in the regulation of various cell functions [34]. In addition, SPRY1 has been reported to regulate neuronal apoptosis [22,35] and predicted as the potential downstream target of miR-187 by using the TargetScan software, which indicated that miR-187 might alleviate PTZ-induced epilepsy in rats by targeting SPRY1. However, there are still no literature reports of a role of SPRY1 in the development of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…They also reduced ETS-1 expression and cell hypertrophy. Previous studies suggested that miRNA-regulated cytokine production is mediated by modulating AKT/NF-κB ( Zhao et al, 2019 ). miRNA-29a regulates lipopolysaccharide-induced inflammatory responses in murine macrophages through the Akt1/NF-κB pathway ( Tang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%